Platelet activation and prothrombotic mediators at the nexus of inflammation and atherosclerosis: Potential role of antiplatelet agents. (January 2021) - Lordan, Ronan; Tsoupras, Alexandros; Zabetakis, Ioannis
Abstract: Platelets are central to inflammation-related manifestations of cardiovascular diseases (CVD) such as atherosclerosis. Platelet-activating factor (PAF), thrombin, thromboxane A2 (TxA2 ), and adenosine diphosphate (ADP) are some of the key agonists of platelet activation that are at the intersection between a plethora of inflammatory pathways that modulate pro-inflammatory and coagulation processes. The aim of this article is to review the role of platelets and the relationship between their structure, function, and the interactions of their constituents in systemic inflammation and atherosclerosis. Antiplatelet therapies are discussed with a view to primary prevention of CVD by the clinical reduction of platelet reactivity and inflammation. Current antiplatelet therapies are effective in reducing cardiovascular risk but increase bleeding risk. Novel therapeutic antiplatelet approaches beyond current pharmacological modalities that do not increase the risk of bleeding require further investigation. There is potential for specifically designed nutraceuticals that may become safer alternatives to pharmacological antiplatelet agents for the primary prevention of CVD but there is serious concern over their efficacy and regulation, which requires considerably more research.